Development of caninized anti-CTLA-4 antibody as salvage combination therapy for anti-PD-L1 refractory tumors in dogs - Maekawa, Naoya; Konnai, Satoru; Watari, Kei; Takeuchi, Hiroto; Nakanishi, Takeshi; Tachibana, Taro; Hosoya, Kenji; Kim, Sangho; Kinoshita, Ryohei; Owaki, Ryo; Yokokawa, Madoka; Kagawa, Yumiko; et al. (Frontiers in Immunology, 2025)
Immune checkpoint inhibitors (ICIs) are widely used for cancer immunotherapy; however, the clinical efficacy of anti-PD-1/PD-L1 monotherapy is generally limited, highlighting the need to develop combination therapies. Dogs develop spontaneous tumors in immunocompetent settings, and anti-PD-1/PD-L1 antibodies exert similar clinical benefits. However, no clinically relevant anti-CTLA-4 antibody has been reported, limiting the value of canine tumors as comparative models for human ICI research. Here, canine CTLA-4 was molecularly characterized, and a caninized anti-CTLA-4 antibody (ca1C5) that blocks CTLA-4/ligand binding was developed. Treatment with ca1C5 increased cytokine production in canine immune cell cultures, and the immunostimulatory effect was enhanced when used in combination with the anti-PD-L1 antibody c4G12. As a proof-of-concept, a veterinary clinical study was conducted to demonstrate the safety and clinical efficacy of anti-CTLA-4 antibody as salvage combination therapy in dogs with advanced tumors refractory to prior c4G12 monotherapy. The combination treatment (c4G12 plus ca1C5) was well-tolerated, and evidence of antitumor activity was observed in one dog with oral malignant melanoma. Further studies are warranted to advance veterinary care for dogs and to better characterize canine ICI models for human onco-immunology research.